2016
DOI: 10.1521/pedi_2015_29_189
|View full text |Cite
|
Sign up to set email alerts
|

Comparing External Correlates ofDSM-5Section II and Section III Dimensional Trait Operationalizations of Borderline Personality Disorder

Abstract: The current study evaluated the relative associations of the DSM-5 Section II operationalization of Borderline Personality Disorder (BPD) and dimensional traits included in a diagnosis of BPD in DSM-5 Section III with conceptually relevant external criterion variables. It is important to determine whether or not Section II BPD and constellation of Section III BPD traits have similar positions in the nomological network representing the BPD construct. Moreover, it is important to determine whether or not the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…Finally, there is evidence that the AMPD BPD trait profile accounts for some of the same external correlates (i.e. non-PD symptoms, behaviours, and life history variables) as traditional Section II BPD (Anderson, Sellbom, Sansone, & Songer, 2016;Miller, Few, Lynam, & Mackillop, 2015). No study, however, has examined the relation between the AMPD BPD trait profile and IPV perpetration, and this is the first main aim of the current study.…”
Section: Dsm-5 Alternative Model For Personality Disordersmentioning
confidence: 94%
See 1 more Smart Citation
“…Finally, there is evidence that the AMPD BPD trait profile accounts for some of the same external correlates (i.e. non-PD symptoms, behaviours, and life history variables) as traditional Section II BPD (Anderson, Sellbom, Sansone, & Songer, 2016;Miller, Few, Lynam, & Mackillop, 2015). No study, however, has examined the relation between the AMPD BPD trait profile and IPV perpetration, and this is the first main aim of the current study.…”
Section: Dsm-5 Alternative Model For Personality Disordersmentioning
confidence: 94%
“…As such, it was expected that both traditional and AMPD operationalisations of BPD would be associated with IPV perpetration in this study. Further, considering previous research showing that traditional and AMPD operationalisations of BPD are conceptually overlapping constructs (Sellbom, Sansone, et al, 2014), and have similar associations with other BPD relevant antisocial behaviours (Anderson et al, 2016), it was predicted that AMPD BPD scores would be equally as associated with IPV perpetration criteria as traditional BPD scores.…”
Section: Studymentioning
confidence: 99%
“…Several studies have been conducted demonstrating the incremental validity of maladaptive traits above and beyond DSM-5 section II PDs when predicting treatment planning [278], general PD severity [279], disability [235], social cognition deficits [280], and aggression [244]. Some research focused on the incremental validity of selected trait facets above and beyond specific PDs when predicting external criterion variables [236,281,282]. Moreover, two studies indicated that maladaptive traits may have incremental validity for predicting psychosocial impairment [283] or disability and symptoms [284] when controlling for general personality traits and section II PDs.…”
Section: Incremental Validitymentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20] Studies particularly focusing on BPD have found a large overlap between latent representations of the Section II and Section III BPD models 21 and that the BPD Section III trait profile accounts for the same range of internalizing and externalizing behaviours associated with traditional Section II BPD operationalization. 22 Additionally, it has been clarified that Cognitive and perceptual dysregulation 21 and Suspiciousness 20 augment this prediction by mapping onto the stress-induced symptoms of dissociation and paranoia, respectively, which comprise important elements of BPD. 23 These findings indicate that more parsimonious constellations of traits may better represent BPD.…”
Section: Limitationsmentioning
confidence: 99%